The effect of Banate Bay Resource Management Council, Inc. in the political participation and socio-economic development of the project participants in Brgy. Talokgangan, Banate, Iloilo - Gallo, Anne S.
The co-management principle enables local governments to initiate collaborative efforts to manage the coastal resources. This involves the sharing of vison, resources, and expertise to attain the goal of sustainable development and empowerment of the people in the community. The Banate Bay Resource Management Council Inc. (BBRMCI) is the first LGU initiated community resource management program in the province of Iloilo, which includes the municipalities of Banate, Anilao, Barotac Nuevo and Barotac Viejo. It reflects that a collaborative effort between locl governments is crucial in achieving sustainable coastal resource management., This study aimed to (1) find out the legal framework and institutions which provide the foundation for the structure and foundation of BBRMCI, (2)identify the development programs, strategies and resources that BBRMCI employed in Barangay Talokgangan, Banate and (3)evaluate the perception on the effect of the programs in their political participation and socio-economic development. The methods applied to answer the objectives of the study include secondary data analysis, key informant interview, survey questionnaire and focus group discussion. The survey questionnaire was designed to elicit fisherfolk's perception on the extent of their participation and benefits acquired. The questions included their participation in planning implementation, monitoring, benefits acquired and their assessment of the program's effectiveness. The respondents of the study include the BBRMCI personnel, the barangay officials and the active members of the fisherfolk's organization and BFARMC. The BBRMCI personnel were asked about the programs that were implemented in the barangay and the problems that they have encountered. The barangay officials were interviewed regarding the impact of the program in the barangay while the active members were made to answer the questionnaires. The implications of their answers were clarified through focus group discussions. This study observed that the impact of BBRMCI is more remarkable in terms of improving the awareness of the people on the importance of coastal resources than providing alternative livelihood to the fisherfolks. There are mainly three factors why BBRMCI is not successful in attaining its objective of providing alternative livelihood and empowering the fisherfolks. These include the lack of monitoring on the outcome of the projects implemented, the delay of funds allocated for a certain project and the conflict in the interest between the PO and the BFARMC.